2017
DOI: 10.1016/j.sjbs.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Foot care practices of diabetic patients in Saudi Arabia

Abstract: Diabetic foot is a serious complication that causes lower extremity amputations. The aim of this study was to identify the patient’s awareness about risk factors for diabetic foot disease and to explore the knowledge and foot care practices among diabetic patients in a Saudi population. This cross-sectional study was conducted in King Khalid University Hospital (KKUH), King Abdulaziz University Hospital (KAUH), King Fahad Medical City, National Guard Hospital, Military Hospital, and Prince Salman Hospital capi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 17 publications
2
24
0
2
Order By: Relevance
“…Accordingly, the educational level was significantly associated with good knowledge and impacts the care of the diabetic foot injury (17) . Other results were constituent with our results where the most proper knowledge was found among the most educated subjects (4,22,23) .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Accordingly, the educational level was significantly associated with good knowledge and impacts the care of the diabetic foot injury (17) . Other results were constituent with our results where the most proper knowledge was found among the most educated subjects (4,22,23) .…”
Section: Discussionsupporting
confidence: 92%
“…Also, the present study showed that more than 25% of adult populations were suffering from diabetes and this rate was supposed to be doubled (3) . Diabetic foot also represented a major health problem of high mortality and morbidity rates (4) . Also, diabetic foot prevalence was 8-17% among diabetic patients with higher rates of amputations caused by diabetes than other causes including foot ulcers and non-traumatic causes (5,6) .…”
Section: Introductionmentioning
confidence: 99%
“…the educational level (p=0,001) and household income (p=0,001) of the participants had shown an impact on patients' knowledge about diabetic foot injury .The results of our study exposed that the most educated patients are the most knowledgeable about diabetic foot injuries, which come in consistence with the results of other studies. [3,6] The majority (57,8%) of responders were on oral hypoglycemic drugs alone or in combination with insulin (21,7%). A smaller number (15,0%) were on insulin therapy alone.…”
Section: Discussion:-mentioning
confidence: 99%
“…Annually around 3.2 million deaths in the world occurs as result of Diabetes mellitus complications. (3)(4) 20 percent of diabetic hospitalizations are attributed to diabetic foot problems. The risk of lower limb amputation is found to be 10 to 15 times higher among diabetic patients compared with non-diabetics.…”
Section: Introduction and Background:-mentioning
confidence: 99%
“… 19 Another hospital-based, cross-sectional study conducted in Saudi Arabia by Odhayani et al showed that having little or no knowledge about the risk factors, future complications, and foot care in diabetes worsen the condition. 20 …”
Section: Factors Contributing To Diabetes and Associated Dry Gangrenementioning
confidence: 99%